2013
DOI: 10.1016/j.jcrc.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the quality of interdisciplinary rounds in the intensive care unit

Abstract: The quality of IDRs in the ICU can be reliably assessed for patient plan of care and process with the IDR Assessment Scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
0
22
1
Order By: Relevance
“…Mostly surveys based on self report questionnaires have been used to address the different perspectives 13,21,22. Within self report surveys many options exist, further complicating comparability of study results 15.…”
Section: Discussionmentioning
confidence: 99%
“…Mostly surveys based on self report questionnaires have been used to address the different perspectives 13,21,22. Within self report surveys many options exist, further complicating comparability of study results 15.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing complexity of critical care, with its many shared tasks and overlapping activities, demands effective ways of organising the related work meaning that the multidisciplinary team needs to communicate effectively to ensure seamless quality care. However, given the intensive nature of work in these units, the traditional ward round may sometimes seem too time consuming (Ten Have et al ., ). General ward rounds have been found to take anything from 90 to 420 minutes to conduct, with an average time spent on each patient of 8 minutes (Herring et al ., ).…”
mentioning
confidence: 99%
“…While it is our position that some aspects of the overall ritual are valuable, the process and its components need to be questioned as certain elements are being carried on regardless of the changes in society ‘that make the routine no longer necessary’ (Schmahl, , p.75). There are many ways to increase the effectiveness of the ward round, including checklists to ensure that all required elements are included (Herring et al ., ; Ten Have et al ., ); electronic and virtual meetings (Dube et al ., ); nurse only rounds (Aitken et al ., ; Catangui and Slark, ) and “hourly” or “intentional rounding” by nurses (Harrington et al ., , p.1). The latter hourly rounding, now popular in the UK (Snelling, ), appears to improve patient satisfaction and increase efficiency of nursing work (Harrington et al ., ), although the evidence base for this appears somewhat limited (Snelling, ).…”
mentioning
confidence: 99%
“…An effective rounding team requires a vested interest by the facilitator and participants and a commitment to the time it takes to execute this process. 7 The literature reports that formal opportunities for shared decision making and forums that foster communication and collaboration between nurses and their medical colleagues are mutually beneficial. 8 Studies have demonstrated that effective physician-nurse collaboration improves staff satisfaction and patient health outcomes through shared patient management decisions.…”
Section: See the Related Editorial On Page 471mentioning
confidence: 99%